Clinical significance of cough and wheeze in the diagnosis of asthma. Issue 6 (December 1996) - Kelly, Y J; Brabin, B J; Milligan, P J; Reid, J A; Heaf, D; Pearson, M G
Abstract : OBJECTIVES: (1) To determine the prevalence of cough, wheeze, and breathlessness, both as single symptoms and in combination, in primary schoolchildren and their relation to doctor diagnosed asthma. (2) To identify in areas with different levels of dust pollution whether questionnaire reported 'cough alone' (without wheeze or breathlessness) had similar risk factors to the questionnaire reported triad of 'cough, wheeze, and breathlessness'. SUBJECTS AND METHODS: Two cross sectional community surveys of primary schoolchildren (5-11 years) were performed in 1991 and 1993. Parent completed questionnaires related to socioeconomic and respiratory factors were distributed through 15 schools in three areas of Merseyside, one of which had a relatively high level of dust pollution. Data were analysed to determine the prevalence of different respiratory symptom patterns. Univariate and multiple logistic regressions were used to investigate the associations between respiratory symptom profiles and potential risk factors. RESULTS: The proportions of completed questionnaires that were returned were similarly high in both surveys, 92% in 1991 (1872 of 2035) and 87% in 1993 (3746 of 4288). The proportions of children with different respiratory symptom patterns were similar in the two surveys: in 1991, asymptomatic children 70.1% (1109 of 1583), those with cough alone 8.9% (141 of 1583), and children with the symptom triad of cough, wheeze, and breathlessness 8.3% (132 of 1583); the figures for 1993 were 69.5% (2144 of 3083), 9.2% (284 of 3083), and 7.3% (224 of 3083) respectively. The prevalence of doctor diagnosed asthma increased from 17.4% in 1991 to 22.1% in 1993. The symptom of cough alone was associated with going to school in an area of increased air pollution. The symptom triad of cough, wheeze, and breathlessness was associated with reported allergies, familial history of atopy and preterm birth. In 1991, of children with the symptom of cough alone one in eight were diagnosed asthmatic; twice as many doctors made the diagnosis on this basis in 1993. CONCLUSION: The respiratory symptom of cough alone and cough, wheeze, and breathlessness represent clinical responses to different specific risk factors. Cough alone was associated with the environmental factors of school in the dust exposed zone and dampness in the home, whereas cough, wheeze, and breathlessness related to allergic history and preterm birth, and may be the best surrogate of asthma. Diagnosis of asthma on the basis of cough alone partly explains the increased prevalence of doctor diagnosed asthma, especially in dust polluted areas.